Hajj and ʿUmrah Rituals in Religious Studies: Rodrigues-Harding's Theoretical Framework and Contemporary Media Analysis - Anugrah, Muhammad Dimas; Truna, Dody S.; Waluyajati, Raden Roro Sri Rejeki (UIN Sunan Gunung Djati Bandung, 2026)
The Hajj and Umrah rituals are central acts of worship in Islam, containing intertwined spiritual, social, cultural, economic, and political dimensions. In the context of globalization and advanced modernity, these rituals have undergone significant transformation, from traditional spiritual pilgrimage practices to global religious phenomena mediated by digital technology, the travel industry, and transnational market logic. This study aims to analyze the dynamics of this transformation through the religious studies approach developed by Hillary Rodrigues and John S. Harding, which rejects the reductive dichotomy between insider perspectives (faith, religious experience, and theological commitment) and outsider perspectives (critical academic analysis). This study uses an interdisciplinary qualitative approach with a library research design. Primary data sources include the Qur'an, hadith, and the theoretical works of Rodrigues and Harding, while secondary data sources include scientific journal articles, academic books, and contemporary studies on the Hajj, Umrah, and religion in the digital age. Data analysis is conducted through concept reduction, contextual interpretation, and theoretical synthesis by integrating theological, phenomenological, and sociological perspectives. The results of this study indicate that the Rodrigues–Harding approach allows for a more holistic understanding of the Hajj and Umrah as ritual practices that are simultaneously sacred and social. This study also finds that the commodification and mediatization of rituals in the contemporary era creates a paradox between the ideal of spiritual simplicity and the reality of material splendor, but at the same time opens up new spaces for the formation of global Muslim solidarity, including through digital media. The contribution of this study lies in strengthening the interdisciplinary analytical framework in the study of Islamic rituals that bridges faith and science, and offers a critical reflection on the spiritual meaning of the Hajj and Umrah amidst modern socio-cultural changes.